Damage Stability Study of A 500 DW Ro-Ro Ferry Vessel - Ariany, Zulfaidah; Santoso, Budhi; Sarwoko, Sarwoko; Prasetyo, Nauval Abdurrahman (UI Scholars Hub, 2022)
The development of the crossing transportation industry is currently increasing in the island areas. The use of Ro-Ro type ferry boats is extremely efficient in moving people, goods, and vehicles. The current research focuses on the damage stability of the 500 DWT Ro-Ro ferry, which aims to meet the needs of the Ro-Ro ferry in the archipelago area. The previously existing initial design of a barge hull with a main size Lpp = 40.15 m, B = 12 m, H = 3.2 m, and T = 2.15 m was used to analyze the damage stability condition further. First, the drawings were redrawn. Then, 3D modeling was performed and the tanks were inspected. The processing of the input data design was finally tested under several criteria based on damage stability in SOLAS 2009. This study concluded whether the 500 DWT Ro-Ro ferry design is acceptable considering damage stability. The GZ value is standardized in the scenario of calcge stability of the Ro-Ro ferry as a whole. Attention should be provided to the range of positive stability in intermediate stages considering the forward damage case, wherein the ship departs and the full load experiences failure.